INICIATIVA DE TRIAGEM NUTRICIONAL DE IDOSOS DA ÁREA RURAL DE IJUÍ, RS - ROST, DEBORA; BATTISTI, IARA D. E.; SCHWEIGERT, INGRID D.; BELLÉ, TÂNIA R. L.; MACHADO, LUCIELE D. L.; DALLEPIANE, LOIVA B.; BEIER, LIÉGE L. (Salão do Conhecimento, 2013)
Resumo